2010
DOI: 10.1080/19475721.2010.483337
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal, longitudinal and bathymetric patterns of abundance, biomass of metazoan meiofauna: importance of the rare taxa and anomalies in the deep Mediterranean Sea

Abstract: Quantitative information on the spatial distribution of meiofaunal abundance, biomass and biodiversity (as richness of higher taxa) is summarised from 476 sites of the deep-Mediterranean Sea, at depths ranging from ca. 200 to 4617 m. Meiofaunal abundance (465 AE 31 and 306 AE 24 ind 10 cm À2 at 200-1000 and 1000-2000 m depth intervals) and biomass (125 AE 16 and 119 AE 20 mgC 10 cm À2 at 200-1000 and 1000-2000 m depth intervals) in the bathyal sediments of the Mediterranean Sea are similar to those reported in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 81 publications
(109 reference statements)
4
9
0
Order By: Relevance
“…These values were much higher than those reported by Hong et al (2011) in the adjacent Marian Cove (King George Island). Biomass values were high (up to 2 mg C 10 cm -2 ), comparable to those found in temperate estuaries (Tietjen 1969), and up to two orders of magnitude higher than those reported for deep sea sites (Gambi et al 2010). When the two study sites were compared in terms of meiobenthic densities and community composition, they differed only in summer, with higher values and greater diversity in ST1.…”
Section: Discussionsupporting
confidence: 64%
“…These values were much higher than those reported by Hong et al (2011) in the adjacent Marian Cove (King George Island). Biomass values were high (up to 2 mg C 10 cm -2 ), comparable to those found in temperate estuaries (Tietjen 1969), and up to two orders of magnitude higher than those reported for deep sea sites (Gambi et al 2010). When the two study sites were compared in terms of meiobenthic densities and community composition, they differed only in summer, with higher values and greater diversity in ST1.…”
Section: Discussionsupporting
confidence: 64%
“…As a consequence, higher faunal densities are anticipated for this area. The meiofaunal abundances reported in the present synthesis are indeed lower from those of similar depths in other oceans (for an extensive reference report see Gambi et al, 2010) but comparable to those recorded from similar Mediterranean deep-sea sediments (Tselepides and Lampadariou, 2004;Lampadariou and Tselepides, 2006;Lampadariou et al, 2009;Gambi et al, 2010), yet they fall within a wider range of values. Our data also confirms the prediction of higher faunal densities in the northern Aegean Sea, as the higher meiofaunal density was measured in this area.…”
Section: Standing Stocks In the Deep Seasupporting
confidence: 73%
“…Nonetheless, considerable work carried out over the last three decades on the deep Mediterranean meiofauna has advanced our knowledge on the smallest but most abundant metazoans of the sediments (extensive bibliographic references reported in Danovaro et al (2010) and Gambi et al (2010)). Following major trends in ecology, recent investigations have sought for latitudinal, longitudinal and bathymetric patterns of meiofauna (Lampadariou and Tselepides, 2006;Danovaro et al, 2009aDanovaro et al, , 2010Gambi et al, 2010), while few study differences in meiofaunal patterns among deep-sea habitats (Danovaro et al, 2009a, b;Vanreusel et al, 2010;Gambi et al, 2010). Danovaro et al (2009a), in a study including samples from Mediterranean slopes and basins, found that meiofaunal diversity in slopes was higher than in deep-sea plains.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent evidence has suggested that this ecosystem is much more temporally and spatially variable than previously thought, with potentially important implications for biodiversity patterns (Lampitt et al, 2010;Pusceddu et al, 2010Pusceddu et al, , 2013Rex & Etter, 2010). Several mechanisms have been invoked to explain the spatial patterns of biodiversity: (1) sediment grain size and substrate/ habitat heterogeneity (Etter & Grassle, 1992;Danovaro et al, 2009Danovaro et al, , 2010Bongiorni et al, 2010;McClain & Barry, 2010;Vanreusel et al, 2010;Zeppilli et al, 2012); (2) productivity (Smith et al, 2008;Lampitt et al, 2010;Tittensor et al, 2011;McClain et al, 2012); (3) food resources (Danovaro et al, 2008b;Gambi et al, 2010); (4) oxygen availability (Diaz & Rosemberg, 1995); (5) water currents (Lambshead et al, 2001); and (6) occasional catastrophic disturbances (Levin et al, 2001;Pusceddu et al, 2010Pusceddu et al, , 2013. Nonetheless, all of these factors are subjected to strong scientific debate because they are often sitespecific and constrained by local (or regional) conditions (Levin et al, 2001).…”
Section: Introductionmentioning
confidence: 99%